Crosslinguistic encounters in language acquisition typical and atypical development - Babatsouli, Elena; Ingram, David 1944-; Muller, Nicole 1963- (Communication disorders across languages, 2018)
"This book presents diverse, original research studies on typical and atypical child language acquisition in monolingual, bilingual and bi-dialectal settings, with a focus on development, assessment and research methodology. It will be of interest to researchers, clinical linguists, language pathologists and graduate students"--Provided by publisher.